PEMBINAAN AGAMA ISLAM DI PESANTREN MUNTASIRUL ULUM MAN YOGYAKARTA III (Tinjauan Psikologi Humanistik-Religius) - Hamruni, Hamruni (Jurnal Pendidikan Agama Islam, 2016)
Muntasyirul Ulum Boarding School is dormitory for students MAN Yogyakarta III. Coaching materials integrated with lessons in Yogyakarta MAN III, including deepening the material in the form of religion and religious formation of creative and independent character. Serious coaching from Boarding School is done by providing guidance, either individually or in groups. Individual coaching aimed at guiding students through a turbulent adolescence. Guidance also be directed so that students can carry out their duties as students, have an independent person and is able to actualize the potential and talent to be individual resilient in the face of adversity. In addition, the guidance also seeks to equip and nurture students to become strong personal faith. By using a method that is inspiring dialogue, the boarding seeks to educate and equips them with the nature of humanity, tolerance and pluralism. This is in line with the concept of religion in fostering humanistic attempt that students are not only able to do the actualization of the material, but also embodies adherence to the revelation. Keywords: Humanism, actualization,tolerance.